Cementless Metaphyseal Sleeve Fixation in Revision Knee Arthroplasty: Our Experience with an Arabic Population at the Midterm - Abdulrahman D. Algarni (Advances in Orthopedics)
Objective. Metaphyseal sleeve (MS) fixation in revision knee arthroplasty (RKA) among Western populations has been reported with very encouraging outcomes. The aim of this study was to report our experience with the use of MS in RKA among an Arabic population. Clinical and radiographic outcomes and implant survivorship were reported at a minimum follow-up of 2 years and a mean follow-up of 4.1 years. Methods. A retrospective analysis was conducted on prospectively collected data of patients who underwent RKA with a MS in combination with a cementless stem (femoral or tibial). Range of motion (ROM) and Knee Society Score (KSS) were obtained pre- and postoperatively. Complications, occurrence of stem-tip pain, and implant survival were documented. Knee radiographs were obtained to evaluate the alignment and osseointegration or loosening of the MS. Results. A total of 52 sleeves (27 tibial and 25 femoral) implanted in 27 RKAs (27 patients) were included. The mean follow-up period was 4.1 ± 1.8 (2–7.5) years. Postoperatively, the ROM improved from 89.3 ± 9.2 to 106.3 ± 11.4 (p = 0.19) and the KSS also significantly improved, from 102.9 ± 35.6 to 130.2 ± 33.7 (p < 0.001). One patient (3.7%) developed heterotopic ossification, and another one (3.7 %) had a stem-tip pain on the tibial side; both were managed conservatively. One patient (3.7 %) sustained a fracture and required reoperation. None of the sleeves showed progressive radiolucent lines, and none required revision. The aseptic survivorship and overall survivorship at a mean of 4.1 years were 100% and 96.3%, respectively. Conclusion. MS provided successful midterm outcomes that were maintained in obese patients with different levels of constraint. Our series supports their use as a viable option in RKA.